Reducing the Waste of Active Power by Choosing the Right Reactive Power Source - Sharobiddinov Mirzokhid Shakhobiddin ugli; Tokhtasinov Saidislomkhon Khasankhon ugli (Zien Journals, 2023)
The research work on the correct selection of the place of installation of the reactive power source and reduction of the waste of active power, taking into account the consumption of reactive power in consumers, is covered.
Keywords: quality indicators; reactive power; reactive power condensation